2019
DOI: 10.1063/1.5059554
|View full text |Cite
|
Sign up to set email alerts
|

Laser induced fluorescence studies on the distribution of surfactants during drop/interface coalescence

Abstract: The spatiotemporal distribution of fluorescent surfactants on the merging interfaces during the coalescence of an aqueous drop with an organic/aqueous flat interface was studied experimentally with high-speed laser induced fluorescence. The aqueous phase was a 46% glycerol solution, while the organic phase was a 5 cSt silicone oil. A fluorescently tagged surfactant was used at a concentration of 0.001 mol/m 3 in the aqueous phase. To vary the concentration of surfactants on the interfaces, the drop and the fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Recently, the experimental work performed by Dong et al. (2019) suggested that the presence of surfactants induces the rupture of the interface (i.e. hole formation) in an off-axis location at high Bond numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the experimental work performed by Dong et al. (2019) suggested that the presence of surfactants induces the rupture of the interface (i.e. hole formation) in an off-axis location at high Bond numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Current understanding of the coalescence dynamics in such surfactant-laden systems came from Dong, Weheliye & Angeli (2019), who experimentally showed for the first time surfactant concentration profiles for systems characterised by high Bond numbers. Additionally, they suggested that surfactants have a strong effect on the interfacial dynamics inducing interfacial rupture (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A stopwatch with an accuracy of 0.01s was used to measure the rest times. It was previously found that about 50 runs were sufficient to capture the distribution of the rest times of the drops with a stationary interface (Dong et al 2017(Dong et al , 2019). In the current experiments, around 200 runs were conducted for each set of conditions to reduce uncertainties caused by the moving interface.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…When a drop coalesces with a stationary interface, a meniscus is created immediately after the film rupture which expands rapidly until the liquid in the drop completely merges with the bulk homophase. The expansion of the meniscus is resisted by the viscosity of the fluids at the initial stages, and later by the inertia of the liquids Aarts & Lekkerkerker (2008); Murano & Okumura (2018); Dong et al (2019). It was found, however, that when drops coalesce with moving interfaces, the trapped film, before it fully drains, can break in drop strings where different size drops form connected with thin threads.…”
Section: Oil Entrainmentmentioning
confidence: 99%
See 1 more Smart Citation